Production of carrageenan by different strains of Kappaphycus alvarezii cultivated in Serang, Indonesia - Zakaria, Anas; Rahman, Egi Nurul; Ramani, Ulin Noor; Manurung, Robert; Mohamad Puad, Noor Illi; Abduh, Muhammad Yusuf (IIUM Press, 2019)
Kappaphycus alvarezii is one of the main seaweeds cultivated in Indonesia. Its use as a raw material for the kappa-carrageenan industry has increased its cultivation activities. However, standard cultivation protocol for Kappaphycus alvarezii has yet to be well-documented, particularly on strain selection for kappa-carrageenan production. There are various strains of Kappaphycus alvarezii grown in Indonesia, specifically in Serang, Banten such as green, red, and yellowish green strains. In this study, growth rate, carrageenan yield, and gel strength from different strains of Kappaphycus alvarezii were investigated. It was observed that the specific growth rate of green type (4.14% /day) differed significantly from the other two types (red; 3.41% /day and yellowish green; 3.47% /day). The red type had the highest yield of carrageenan (45.16%) followed by yellowish green (36.66%) and green strain (33.67%). Gel strength was not significantly affected by the strain variations where the observed values for yellowish green, green, and red strain were 344.46, 316.91 and 313.10 g/cm2 , respectively. Green Kappaphycus alvarezii had the highest biomass (0.27 g/cm/d) and carrageenan productivity (0.012 g/cm/d). It can be concluded that the green strain of Kappaphycus alvarezii is the most suitable for cultivation in Serang, particularly for the kappa-carrageenan industry.